The Four Deadly Sins of Implicit Attitude Research - Sherman, Jeffrey W.; Klein, Samuel A. W. (Frontiers in Psychology, 2021)
In this article, we describe four theoretical and methodological problems that have impeded research on and popular understanding of implicit bias. The problems all revolve around assumptions made about the relationships among measures (indirect vs. versus direct), constructs (implicit vs. explicit attitudes), cognitive processes (e.g., associative vs. propositional), and features of processing (automaticity vs. control). These assumptions have confused our understandings of exactly what we are measuring, the processes that produce implicit bias, the meaning of differences in bias across people and contexts, the meaning of bias change in response to intervention, and how bias predicts behavior. We describe formal modeling as one means to address these problems, and provide illustrative examples. Clarifying these issues has important implications for our understanding of who has implicit bias and why, when bias is likely to be particularly problematic, how we might best try to diminish bias, and what interventions are best suited to minimize the effects of bias on behavior.